Research on How Emotional Expressions of Emotional Labor Workers and Perception of Customer Feedbacks Affect Turnover Intentions: Emphasis on Moderating Effects of Emotional Intelligence - Lee, Young Hee; Lee, Suk Hyung Bryan; Chung, Jong Yong (Frontiers in Psychology, 2019)
Previous studies have used various external variables and parameters as well as moderator variables such as emotional intelligence have been to understand emotional labor and its related problems. However, a comprehensive model to study such variables’ correlations with each other and their overall effect on emotional labor has not yet been established. This study used a structural equation model to understand the relationship between employees’ expression of emotional labor and perception of customer feedbacks. The study also looked at how the perception of customer feedback affects emotional exhaustion in order to understand how emotional exhaustion affects job satisfaction and turnover intentions. Further, in order to fully understand the effects of emotion on emotional labor at the service contact points, this study developed and tested a model of emotional labor with four factors of emotional intelligence as moderating factors. Five hundred and seventy nine emotional labor workers in service industries in the United States were collected and 577 valid survey results have been analyzed. The result shows that there exists moderating effects of emotional intelligence on how employees’ Deep Acting and Surface Acting recognize customers’ reactions, both positive and negative, that would affect employees’ Emotional Exhaustion and Job Satisfaction, and hence, Turnover Intention. The result suggests that employees with better understanding of their own emotions, although they are more likely to recover from emotional exhaustion, experience a greater negative effect when there is a discrepancy between what they feel and how they should act.